Optimal Design of the Pitching Mechanism Considering the Influence of Erecting Angle Curves - Yuan Yi; Deng Wenzhu; Wu Bude; Wang Yuqi; Lu Wei; Ding Yuli (Jixie chuandong)
The erecting angle curve directly affects the angle acceleration of the pitching mechanism of the rocket, and then directly affects the instantaneous thrust and instantaneous power of the pitching mechanism, ultimately affects the best arrangement of the pitching mechanism. As the requirements of the pitching mechanism for smooth start & stop and erecting time, the angular acceleration of the pitching mechanism can't be ignored, and the optimal design of the pitching mechanism considering the influence of the erecting angle curve was proposed. The key parameters of the erecting angle curve and its restrictions were analyzed, the influence of the vertical angle curve on the instantaneous thrust & power of the electric cylinder was analyzed, the mathematical mode for the optimization of the pitching mechanism considering the influence of erecting angle curve was established, and the optimal pitch mechanism layout and the erecting angle curve were obtained by using the fmincon function based on the sequential quadratic programming (SQP) algorithm in Matlab sofware. Erecting test results of a rocket launcher show that the optimal design of the pitching mechanism considering the influence of the erecting angle curve can effectively reduce the maximum power of the electric pushrod, rather than reduce the maximum thrust of the electric pushrod.